THE FRENCH CULTURAL SPACE IN THE ASPECT OF AMERICANIZATION: A LINGUOCOGNITIVE PERSPECTIVE - Klymenko, Lada; Burmistenko, Tetiana (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2025)
The article presents the results of a comprehensive study on the impact of Americanization on the evolution of France’s cultural space. It analyzes the process and outcomes of the incorporation of American linguocultural realities into the formation of the country’s linguistic worldview. It has been established that American expansion has contributed, on the one hand, to the development of a different mode of linguistic thinking under the influence of linguistic unification due to English, and on the other, to the modification of the conceptual framework of the recipient French culture. The sectors of the French cultural space most sensitive to the adaptation of Americanisms have been those lacking native analogs or equivalents, such as business, lifestyle, technology, and culture. The key theoretical foundation of this study is the concept of linguocultural transfer, which refers to the process of borrowing words, expressions, images, and culturally specific concepts from one culture into another. This process is accompanied by the assimilation, hybridization, or competition of these elements within the recipient culture. Assimilation involves the introduction of culturally specific concepts into the French cultural space along with their original designations (direct borrowing of terms, calquing), whereby they remain phenomena of the source culture. Hybridization fosters the creation of new meanings and concepts through intercultural conceptual integration, which modifies the semantic content of a concept, leading to the formation of new conceptual categories. Competition manifests in the critique of Americanization as a threat to French identity and resistance to American realities. The cognitive effects of linguocultural transfer are evident at multiple levels, altering the worldview of the recipient culture, including changes in everyday practice scenarios and established norms. This process gives rise to hybrid cultural models that combine local and borrowed elements. Linguocultural transfer induces transformations in the linguistic, discursive, and social structures of French culture, contributing to the formation of a stereotyped consciousness and reinforcing clichés under the influence of the ideals of the American Dream, which serves as a cognitive prototype of Americanization.________________References:• Berstein,, & Milza, P. (1991). Histoire de la France au XXè siècle, 1944–1958. Paris: Complexe.• Buttjes,, & Byram, M. (Eds.). (1990). Mediating Languages and Cultures: Toward an Intercultural Theory of Foreign Language Education. Clevedon: [Publisher].• Colman, M. (2008). A Dictionary of Psychology (3rd ed.). Oxford: Oxford University Press. https://doi.org/10.1093/acref/9780199534067.001.0001• Ducrot,, & Todorov, T. (1972). Dictionnaire encyclopédique des sciences du langage. Paris: Seuil.• Duroselle,-B. (1976). La France et les États–Unis des origines à nos jours. Paris: Seuil.• Espagne,, & Werner, M. (1991). Transferts: Les relations interculturelles dans l’espace franco-allemand (XVIIIe–XIXe siècles) [Transfers: Intercultural Relations in the Franco-German Space (18th–19th Centuries)]. Annales. Économies, Sociétés, Civilisations, 46, 911–912. https://doi.org/10.1017/S0395264900069067• Etiemble, (1964). Parlez–vous franglais? Paris: Gallimard.• Fauconnier, G., & Turner, M. (1998). Conceptual Integration Networks. Cognitive Science, 22(2), 133–187. https://doi.org/10.1207/s15516709cog2202_1• Graddol, (2000). The Future of English? (2nd ed.). London: [Publisher]. http://cfaculty.chuo–u.ac.jp/~mikenix1/co/we/Future_of_English.pdf• Hock, H. (1991). Principles of Historical Linguistics (2nd ed.). Berlin: Mouton de Gruyter.• Held,, & McGrew, A. (1998). The End of the Old Order? Globalization and the Prospects for World Order. Review of International Studies, 24, 219–243. https://doi.org/10.1017/S0260210598002191• Kuisel, F. (2011). The French Way: How France Embraced and Rejected American Values and Power. Princeton: Princeton University Press.• Lazar, (1986). Les batailles du livre du Parti Communiste français (1950–1952). Vingtième Siècle. Revue d’histoire, April–June.• Moffett, E. (1907). The Americanization of Canada. New York: Columbia University.• Ory, (1984). Mickey Go Home! La désaméricanisation de la bande dessinée (1945–1950). Vingtième Siècle. Revue d’histoire, 4, 77–88. Paris: Sciences Po University Press.• Prochasson, (1993). De la culture des foules à la culture de masse. In A. Burguière & J. Revel (Eds.), Histoire de la France, les formes de la culture (pp. [page numbers]). Paris: Seuil.• Samovar,, Porter, R., & Jain, N. (1991). Understanding Intercultural Communication. Belmont, CA: Wadsworth.• Schleicher, (1860). Die deutsche Sprache. Stuttgart: J. G. Cotta’scher Verlag. https://doi.org/10.11588/diglit.61330#0114• Sonntag, K. (2003). The Local Politics of Global English: Case Studies in Linguistic Globalization. Lanham, MD: Lexington Books.• Tournès, (1997). L’américanisation de la culture française ou la rencontre d’un modèle culturel conquérant et d’un pays au seuil de la modernité. Historiens/Géographes, 358, 65–79.• Winock, (1982). U.S. Go Home: L’antiaméricanisme français. L’Histoire, November.
Keywords: Americanization, national cultural space, borrowing, linguocultural transfer, conceptual integration